Collapse of an online social network: The blame on social capital - László Lőrincz; Júlia Koltai; Anna Fruzsina Győr; Károly Takács (Hungarian Academy of Sciences, Institute of Economics, 2017)
The rise and popularity of online social networks is a recent phenomenon. In this study, we analyze the reasons and mechanisms behind the collapse of an online social network (OSN), iWiW. Significant cascading mechanisms have been identified in the pattern of abandoning the site at its peak of popularity and after. It is of key importance to study who were the key actors that started these cascades and abandoned the site early compared to others in their network. We contrasted explanations based on preserving accumulated social capital vs. building new social capital with motives influenced by innovativeness. On the one hand, those who are well embedded in their existing network have more to lose. On the other hand, people might want to escape from redundancy and indebtedness indicated by a high local clustering coefficient. We find with heterogeneous choice models that lower degree and a high local clustering are associated with early abandonment. The significant effects of age and innovativeness that depend on the life stage of the OSN indicate that mechanisms related to social capital are not the only reasons for the collapse.
Keywords: D70; D85; 330; online social networks; social capital; innovation; embeddedness